PENGARUH DOSIS PUPUK ORGANIK SARI ALAM DAN PUPUK PETROBIO TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays sacharata) VARIETAS TALENTA - Fajar Rizki Sudibyo; Pamuji SU; Nunuk Helilusiatiningsih (Jurnal Ilmiah Hijau Cendekia, 2018)
Sweet corn needs continue to increase along with the increase in population and the increase in processed foods made from sweet corn. In Indonesia the yield of sweet corn is classified as low, which is 3.5 tons / ha, while the potential for sweet corn production currently reaches 8.31 tons / ha. To meet the needs of sweet corn in the community that continues to increase, it is necessary to have an effective cultivation system by utilizing organic fertilizer, so that we get healthy products, safe for public health and the environment. This study aims to determine the interaction between the dose of Sari Alam organic fertilizer and Petrobio fertilizer on the growth and production of sweet corn (Zea mays sacharata) Talenta variety. In this study using factorial randomized block design. Observative vegetative parameters include plant height, stem diameter, and leaf area. While the harvest parameters include weight of corn cobs with weights, weight of corn cobs without weights, cob length without weights, Sugar Level Analysis (%). From the results of the study there was a very real interaction on the combination treatment of organic fertilizer dosage of natural juice and petrobio S3P2 fertilizer (dosage of natural extract 44gr / plant, petrobio dose 0.5gr / crop) at the observation of plant height at the age of 21 days and stem diameter at 28 days . There was a significant effect on the single factor dosage of S3 natural fertilizer organic fertilizer (dose 44gr / plant) on the weight of lobed cob.